Penstrukturan data bagi video asas menggunakan kaedah formal untuk pengekstrakan dan perbandingan video - Fadilah Harun
A multimedia database is a structure and composition of multimedia information for content retrieval. It supports various multimedia data types such as text, images, audio and video. Among all these types of data media, video is the most challenging. This is because the video incorporates all the information from different media types into a single data stream. Multimedia data manipulation is not as easy as using a conventional database. The database can display video clearly, but their problem is to achieve the video data structure itself. This problem occurs when we want to ensure that content data in the database similar with the content specified in the query. Based on previous studies, there are several techniques for structuring data video such as temporal and spatial relationships. All these techniques focused on the design of a good database. However, structuring a video data have some limitations, such as the size and complex object model in a variety of conditions make it difficult to index, search and retrieval of video content. To realize this study, formal method approach will be used to determine the relationship and retrieve the contents of the structure. This study resulted in a framework known as Video Extraction Analyzer v